2018
DOI: 10.1515/pmp-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Progress of Sintering in Ferrous Powder Compacts by In-Situ Measuring the Thermal Conductivity

Abstract: In situ characterization of the sintering process is a difficult task, in particular for systems without pronounced dimensional changes. Dilatometry is not too helpful in those cases, and therefore other properties have to be recorded. In the present study, sintering of ferrous powder compacts was studied in situ by measuring the thermal diffusivity a using a laser flash apparatus. This property is a measure to characterise the heat flow through a material; it depends on the contact area between the particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…In contrast to the pronounced differences of the nitrogen content (by a factor of about 250), the oxygen content is virtually identical, proving that carbothermal reduction of the oxides is not affected by the atmosphere, which agrees with previous experiments (see e.g. [5,24]). Tab.1.…”
Section: Sintering Studiessupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to the pronounced differences of the nitrogen content (by a factor of about 250), the oxygen content is virtually identical, proving that carbothermal reduction of the oxides is not affected by the atmosphere, which agrees with previous experiments (see e.g. [5,24]). Tab.1.…”
Section: Sintering Studiessupporting
confidence: 91%
“…Different amounts of carbon were added, namely in a first run a higher content of 0.7% and then 0.08 and 0.3%C (all concentrations given in mass%). The 0.08%C was added to obtain a well sintered material with hardly any oxygen (carbon being required as reducing agent, see [5]) and as low content of carbon as possible after sintering. The higher contents were chosen to check if there are any interactions between carbon and nitrogen in the material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If such a powder compact is studied by thermoanalytical techniques, and the gaseous species formed during sintering are analysed by MS, characteristic reduction 'windows', temperature intervals, are identified in the heating section of the run, which can be detected by the mass signals of the reduction products, m18 for H 2 O and m28 for CO. In principle, CO might also indicate N 2 since the mass number is the same, but CO and N 2 can be easily distinguished by tracking also m12 and m14, respectively, since it has been shown that if CO is formed, the m12 graph is virtually a copy of that for m28, just with lower signal intensity [18].…”
Section: Compacts From Chemically Homogeneous Metallic Systemsmentioning
confidence: 99%
“…[6] Two main problems arise from the presence of surface oxides: 1) oxide layers on the metal powders hamper the progress of neck formation during sintering, because the diffusion of metal atoms through the oxide layers around the metal particles is the rate-determining factor during consolidation progress. [9][10][11] 2) In addition, non-metallic inclusions formed during sintering degrade the material properties of the final product as compared with a bulk material without imperfections. [12,13] The use of pre-alloyed powders is particularly sensitive for surface oxide formation as compared with the sintering of powder mixtures.…”
Section: Introductionmentioning
confidence: 99%